The effect of aquous extract of johar leaves (Senna siamea) injection on survival rate and blood profile of snakehead fish (Channa striata) - Amalia Sutriana; Budianto Panjaitan; Tasya Luthfiah Siddik; Farida Farida; Muhammad Hanafiah; Nuzul Asmilia; Rosmaidar Rosmaidar; Rahmad Rahmad (Depik, 2022)
Aqueous extract of johar leaf contains metabolite compounds such as flavonoids, sponins, tannins, phenols, anthraquinones, anthocyanins, and cardiac glycosides which can be used to substitute commercial antibiotics. The use of aqueous extract of johar leaf has been known to have antibacterial activity in vitro. This study aims to determine the effect of aqueous extract of johar leaves (Senna siamea) injection on survival and blood profile of snakehead fish (Channa striata) in vivo. This research was a laboratory study using a completely randomized design (CRD) with 5 treatments and 3 replications with a total sample of 75 snakehead fish. The fishin KA, KB, KC and KD groups were injected with aqueous extract of johar leaves with concentrations of 10%, 20%, 40%, and 60% respectively, while in KE group the fish was injected with distilled water (control). The parameters of this study were the survival rate and blood profile of snakehead fish. Blood hematology examination included calculation of erythrocyte count, hemoglobin level, and hematocrit percentage, leukocyte count, and thrombocyte count. The research data obtained were analyzed using one-way analysis of variance and followed by Duncan's Multiple Distance test. Injection of aqueous extract of johar leaf did not affect the survival rate of snakehead fish. However, hemoglobin and platelet levels significant decrease in the group given 60% concentration of aqueous extract of johar leaf. It can be concluded that aqueous extract of johar leaf at a concentration of 10%, 20%, 40% is safe to use in snakehead fish.Keywords:Johar leaves extractSnakehead fishBlood profileSurvival rate